An Overview of Agricultural Pollution in Vietnam : The Livestock Sector - Dinh, Tung Xuan (World Bank, Washington, DC, 2018)
In the past 10 years, Vietnam’s population has grown by around 1.03 percent per year, increasing from 83.1 million in 2005 to 93.4 million in 2015. Food demand has also increased rapidly as population and incomes have increased, and food consumption patterns have shifted.Intensification has been the sector’s response to this surge in demand, especially in pig and poultry production, and this pattern has given rise to environmental problems.The objective of the review was to provide a broad national overview on (a) pollution related to livestock development—its magnitude, impacts, and drivers; (b) measures that are currently in place to manage or mitigate waste pollution in different farming systems and the potential for addressing the problems when moving forward; and (c) existing knowledge gaps and directions for future research and interventions.The paper is organized into nine sections. Section one provides the introduction; section two provides an analytical framework; section three presents the findings and discussions, which includes livestock development and intensification of trends and production systems, and waste management practices; section four presents the physical impacts on environment; section five presents the socioeconomic impacts; section six presents the driving factors; section seven discusses interventions; section eight talks about the current knowledge and data gaps; and section nine includes conclusions and recommendations.